Family carers managing personal budgets for adults with learning disabilities or autism. (11th October 2020) - Turnpenny, Agnes; Rand, Stacey; Whelton, Beckie; Beadle‐Brown, Julie; Babaian, Jacinta
Accessible summary: Direct payments can help people with learning disabilities or autism to have good support. Often, family carers manage the direct payments for people who would find this very difficult. We asked family carers who managed direct payments to tell us why they decided to do this and what their experiences were. Family carers told us they found managing direct payments difficult and stressful at first, but this got easier over time. They also said that direct payments helped their family members to have more person‐centred support. Abstract: Background: There are a growing number of people with learning disabilities and autism who access personal budgets in the form of direct payments in England. Although they are often involved in decisions about their support, personal budgets are usually managed by someone else, typically a parent. This study examined the experiences of carers who manage personal budgets for adults with learning disabilities or autism with a particular focus on the challenges of securing suitable support and implications for their own well‐being. Methods: This was a qualitative study using a descriptive phenomenological approach to investigate the lived experiences of family carers who manage personal budgets. We conducted semi‐structured interviews with 13 family carers. Interview transcripts were thematically analysed using the framework approach. Results: Our analysis identified five main themes. The first theme relates to why carers decide to take up a personal budget in the first place and their initial expectations. The second theme, restricted choice, highlights the difficulties in securing adequate support and services in the context of what are often described as "complex needs." The third and fourth themes relate to the tasks involved in managing a personal budget and the challenges associated with the dual role of the carer as a parent and a "professional." The fifth and final theme, mixed emotions, describes the impact on the subjective well‐being of carers. Conclusions: Family carers indicated that the benefits of personal budgets outweighed the difficulties and stress inherent in managing them. They need adequate support to ensure that personal budgets deliver personalised and self‐directed support and greater well‐being, and are sustainable arrangements.